Translation and Psychometric properties of Children Behavior Questionnaire-Very short form: Gender differences on Temperament - Syeda Shamama, Aqsa Shakeel, Syeda Shamama, Aqsa Shakeel (Journal of Rawalpindi Medical College, 2022)
Objective: 1- To translate Children’s Behavior Questionnaire-very short (CBQ) form in Urdu language and to establish its psychometric properties. 2- To study gender differences on subscales of CBQ. Material and Methods: The study was conducted with 279 mothers (working and non-working) and their children (3-7 years) in Rawalpindi, Pakistan. CBQ-very short form was translated into Urdu language as per standard procedure1. Translated scale was given to mothers and available fathers to rate their children on temperament. To establish cross language validation 13 mothers were given both original English CBQ-very short form and translated version with the gap of two months. To study gender differences on three dimensions of temperament between boys and girls (boys = 138, girls = 141) one way ANOVA was run. Results: Results indicated high Cronbach’s alpha reliability α = .80 (total) and .61to .81 for its subscales, high to satisfactory cross language validation (test retest reliability) r =.64* to .86** (p < .05 & .01), and high inter-rater reliability between fathers and mothers r = .38* to .82** (p < .05 & .01). The item total correlations of subscales were also satisfactory. Finding showed that Urdu version of CBQ is highly reliable and valid to be used with Pakistani Children (3-8 years). In addition we found significant gender differences on effortful control, girls being high on effortful control as compared to boys. Conclusion: The study revealed CBQ-very short form- Urdu version as reliable and consistent measure of children’s temperament (3-7years) in Pakistani culture. Findings also support earlier evidence that girls show higher score on effortful control as compared to their counterparts. Key Words: CBQ, Temperament, gender differences, Urdu version.